FLUID PROCESSES IN DIAMOND TO SPINEL FACIES SHALLOW MANTLE - Menzies M.; Chazot G. (My University, 1995)
Topography on the lithosphere-asthenosphere boundary and resultant variations in the architecture of the lithosphere are inextricably linked to heat and mass transfer processes involving the convecting upper mantle. This is primarily accomplished by the movement of silicate and nonsilicate (i.e. carbonate) melts, derivatives of which are trapped in the shallow mantle beneath tectonically active and inactive parts of continents. In diamond facies mantle (180–220 km), melt character is inferred from solid inclusions (e.g. apatite, carbonate, mica) in megacrystic diamonds and the mineralogy and chemistry of diamondiferous peridotites and eclogites. Deep lithospheric processes have involved silicate (K-rich and hydrous) and carbonate melts. In garnet facies mantle (75–200 km) information on melt transfer processes occurs in kimberlite-borne xenoliths, e.g. phlogopite-richterite garnet peridotite, MARID (mica-amphibole-rutile-ilmenite-diopside) pyroxenites and IRPS (ilmenite-rutile-phlogopite-sulphide) pyroxenites. Polybaric fractionation and crystallization of silicate melts in propagating fractures in the lower lithosphere can explain the character of several xenolith suites. Transfer of potassic silicate melts (equiv. kimberlite/lamproite) are thought to be closely linked to the genesis of MARIDs and hydrous garnet peridotites, and, the transfer of alkaline silicate melts (equiv. basalt) may explain the character of IRPS pyroxenites. In spinel facies mantle (<75 km) kaersutite-pargasite-carbonate spinel peridotites and amphibole-mica-apatite pyroxenites constrain the nature and origin of shallow mantle fluid processes. While transfer of mobile silicate (equiv. basalt) melts accounts for the chemistry of many spinel peridotites and pyroxenites, highly mobile carbonate melts are believed to have played a pivotal role in the formation of apatite pyroxenites/wehrlites (converted peridotites) and carbonate-bearing peridotites (reacted wallrock).